Nonlinear Optical Properties of Pure and Ag/Polyaniline Nanocomposite Thin Films Deposited by Plasma Jet - R. Humud, Hammad (Iraqi Journal of Science, 2022)
In present work, the nonlinear optical properties of pure polyaniline and Ag/polyaniline nanocomposite thin films, deposited by plasma jet on glass substrate, were studied through open and closed Z-scan technique using pulse second harmonic Nd:YAG laser of wavelength 532nm, pulse duration of 30 ns and input energy 30mJ. The nonlinear optical properties of pure polyaniline thin films and silver polyaniline nanocomposite thin films prepared at constant gas flow rate 1lm-1 and different silver weight concentration 4, 5, and 10% were studied. The closed aperture Z-scan data indicates that the sign of the refraction nonlinearity is negative for pure polyaniline thin films n2 =11×10-3 cm2/MW and positive nonlinearity for Ag/polyaniline nanocomposite thin films, n2=72×10-3, 66×10-3 and 96×10-3 cm2/MW for silver weight concentration 4, 5, and 10% respectively. The open Z-scan measurements show two photons absorption β=75×103 cm/MW for 4%wt silver concentration and show saturated absorption for pure polyaniline, 5 and 10%wt silver concentration. The transmission spectra obtained by UV-Visible absorption spectra exhibit interference fringes, for the samples with 4% and 5%wt silver concentration which is an indication of the good uniformity and homogeneity of the films.